The multi-criteria evaluation in the location of street vendors in Tibasosa, Boyacá, Colombia - Fajardo Pineda, Luis Felipe; Pava Vargas, Andrés Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper presents an evaluation with multiple criteria of alternative locations for street vending in the municipality of Tibasosa, Colombia. The main objective was to identify the stable location that best suits the productive development needs of informal vendors, in harmony with the other dynamics of the territory -economic sectors, social relations, cultural, spatial and administrative aspects, among others. For this, the Multi-Criteria Evaluation method (MCE) was applied, in which various variables or attributes on space regulations were considered and applied to a specific number of the eventual locations. The research was based on primary information (interviews, surveys and work tables), legal analysis (Territorial Planning Scheme) and on specific studies for each case (distance radius, pedestrian volumes and cost of interventions). As a result, it was identified that the Priest House Parking is the place with the highest correspondence with the proposed objective, since it was the alternative with the highest standardized assessment score of the criteria (0.136). Thus, the article proposes a methodology of great relevance to undertake local public policy processes, in order to identify the ideal location for street vending activities in a territory.